LITERATURE REVIEW: EVALUASI KUALITAS KELENGKAPAN DATA PADA FORMULIR REKAM MEDIS PASIEN DI RUMAH SAKIT - Yula Budi Wardiyana; Mega Purnama Dewi Setiyowati; Ayu Nur Jannah; Agin Gianiska; Harprisiskayani Trisna Lestari; Alief Wijayanto; Rizki Oktaviana Tri Wilujeng; Aninda Nur Laili (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
This study aims to analyze the completeness of inpatient medical record filing using a literature review method. A total of 10 articles were selected from journal databases, grey literature, and hand searching. The research findings indicate variation in the percentage of medical record completeness among the analyzed articles, with some showing high completeness rates and others showing low completeness rates. Factors contributing to incompleteness include errors in form filling and insufficient understanding among medical staff regarding the importance of medical record completeness. Recommendations from this study include the necessity to enhance medical staff's understanding of the medical record filling process, as well as the implementation of better policies and training to ensure optimal completeness in medical documentation. This research contributes to understanding the factors influencing the completeness of inpatient medical records and provides a basis for developing strategies to improve the quality of healthcare services in hospitals.